1994
DOI: 10.1093/nar/22.10.1921
|View full text |Cite
|
Sign up to set email alerts
|

Reproducible DNA fingerprinting with the random amplified polymorphic DNA (RAPD) method

Abstract: Much interest has recently arisen in methods for DNA fingerprinting based on the polymerase chain reaction (PCR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(74 citation statements)
references
References 2 publications
3
68
0
3
Order By: Relevance
“…Several studies have shown that the number of loci amplified with RAPD primers depends on factors such as reagents and reaction conditions, sample conditions, and DNA quality and extraction methods (Williams et al 1990;Black 1993;Ellsworth et al 1993;Kernodle et al 1993;MacPherson et al 1993;Meunier and Grimont 1993;Micheli et al 1994;Gallego and Martinez 1997;Khandka et al 1997). Variations were minimized and amplifications of artifacts in the RAPD profiles were prevented by using heads and legs of individual frozen flies, by using similar amounts of template DNA for PCR runs, by running a negative control in each reaction, and by using 2 batches of each potential primer and AmpliTaq® DNA Polymerase Stoffel Fragment during the replication process.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the number of loci amplified with RAPD primers depends on factors such as reagents and reaction conditions, sample conditions, and DNA quality and extraction methods (Williams et al 1990;Black 1993;Ellsworth et al 1993;Kernodle et al 1993;MacPherson et al 1993;Meunier and Grimont 1993;Micheli et al 1994;Gallego and Martinez 1997;Khandka et al 1997). Variations were minimized and amplifications of artifacts in the RAPD profiles were prevented by using heads and legs of individual frozen flies, by using similar amounts of template DNA for PCR runs, by running a negative control in each reaction, and by using 2 batches of each potential primer and AmpliTaq® DNA Polymerase Stoffel Fragment during the replication process.…”
Section: Discussionmentioning
confidence: 99%
“…Random amplified polymorphic DNA (RAPD) oligonucleotide primers were synthesized and PCR was carried out by using 10 ng genomic DNA as template. 11 …”
Section: Treatment Of Lung Cancer Cell Lines With Differentiation Indmentioning
confidence: 99%
“…Among these RAPD analysis is cheap and easy to apply, although its repeatability is not perfect with respect to amplification products profile. Careful optimization of the RAPD protocol has been shown to increase the reproducibility of the RAPD data (Micheli et al, 1994). This marker system has been extensively used for variability study in various crops.…”
Section: Discussionmentioning
confidence: 99%